Anticonvulsant action of an antagonist of metabotropic glutamate receptors mGluR5 MPEP in immature rats - Lojková, Denisa; Mareš, Pavel (Neuropharmacology, 2005)
Antagonists of type I of metabotropic glutamate receptors exhibit anticonvulsant action in adult as well as immature rodents. To know the anticonvulsant profile of a specific mGluR5 antagonist MPEP in developing rats, two models of epileptic seizures were used. MPEP (10, 20 or 40 mg/kg i.p.) suppressed in a dose-dependent manner epileptic afterdischarges induced by electrical stimulation of sensorimotor cortical area in three age groups (12, 18 and 25 days old). The anticonvulsant action was more expressed in the youngest group than in older animals so that in 25-day-old rats an additional dose of 80 mg/kg was used. In contrast to this marked anticonvulsant action, MPEP at a dose of 40 mg/kg i.p. in 18-day-old rat pups and at doses of 40 and 80 mg/kg in 25-day-old rat pups did not affect episodes of spike-and-wave rhythm elicited by low doses of pentetrazol. Our results delineate the profile of the anticonvulsant action of MPEP and confirm the higher efficacy of this antagonist at early developmental stages in comparison with prepubertal animals.
Keywords: modely nemocí na zvířatech; novorozená zvířata; reakční čas; Analysis of Variance; Reaction Time; zvířata; Rats; elektroencefalografie; Disease Models, Animal; Financing, Organized; Animals, Newborn; Cerebral Cortex; financování organizované; mužské pohlaví; Age Factors; antikonvulziva; Pyridines; Epilepsy; absentní epilepsie; mozková kůra; receptory metabotropního glutamátu; Anticonvulsants; Epilepsy, Absence; Electroencephalography; Rats, Wistar; analýza rozptylu; krysa rodu Rattus; potkani Wistar; Dose-Response Relationship, Drug; věkové faktory; pyridiny; epilepsie; Animals; vztah mezi dávkou a účinkem léčiva; Receptors, Metabotropic Glutamate; elektrická stimulace; Male; Electric Stimulation